Extended sagittal saw cut significantly reduces fracture load in cementless unicompartmental knee arthroplasty compared to cemented tibia plateaus: an experimental cadaver study - Seeger, Jörn Bengt; Haas, Daniela; Jäger, Sebastian; Clarius, Michael (Knee surgery, sports traumatology, arthroscopy, 2012)
PurposePeriprosthetic tibial plateau fractures represent a rare but serious complication in unicompartmental knee arthroplasty and are associated with extended sagittal tibial bone cuts. These can occur during the surgery, weaken the posterior cortex of the tibia and are associated with periprosthetic tibial plateau fractures. Although excellent long-term results have been reported with cemented unicompartmental knee arthroplasty, there is high interest in cementless fixation. The aim of the study was to compare fracture loads of cementless and cemented unicompartmental knee arthroplasty.MethodsTibial components of the Oxford Uni were implanted in six paired fresh-frozen tibiae with a defined extended saw cut (10°) at the dorsal cortex of each specimen. In one set, surgery was performed with cement fixation, and in the other, cementless components were implanted. Vertical loads were then applied under standardised conditions to fracture the specimens.ResultsMedian loads of 3.7 (0.7-6.9) kN led to fractures in the cemented group, whereas cementless fixated tibiae fractured with a median load of 1.6 (0.2-4.3) kN (P = 0.02).ConclusionThe loading capacity in tibiae with cementless components is significantly less compared to cemented fixation. The results show that in case of an extended sagittal bone cut patients especially those with poor bone quality who are treated with a cementless unicompartmental knee arthroplasty are at higher risk for periprosthetic tibial fractures.